Body, Alcohol, and The Quest for Identity: Understanding Youth Drinking Practices in Urban Setting - Carolina Retmawati Putri (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
The phenomenon of alcohol consumption among urban youth is generally viewed negatively as deviant behavior and a moral threat. However, this study seeks to understand this practice through an anthropology of the body approach that highlights the experiences, expressions, and social meanings embodied in the body. This study aims to explain how alcohol consumption practices play a role in the process of identity search, solidarity formation, and negotiation of social and cultural norms in urban spaces. The method used is a qualitative approach through observation and in-depth interviews with young people in urban environments. The results show that alcohol consumption is not solely a form of deviance, but also a performative means to negotiate freedom, strengthen social bonds, and express self-identity amidst social pressures that demand compliance. These findings highlight that the body becomes an arena where personal experiences and social structures intertwine in shaping the meaning of consumption. The novelty of this study lies in its attempt to view alcohol as a positive medium in the formation of identity, solidarity, and self-expression among young people, rather than merely an object of moral violation, thus opening new space for a more reflective understanding of the relationship between the body, culture, and consumption.